Human Biochemistry - Gerald Litwack (Academic Press, 2018)
Human Biochemistry includes clinical case studies and applications that are useful to medical, dentistry and pharmacy students. It enables users to practice for future careers as both clinicians and researchers. The book also provides extensive online support for students to assist with further understanding and comprehension of advanced concepts, including sample questions that will help them prepare for medical exams. In addition, instructor's ancillaries include PowerPoint presentations and testbanks. Offering immediate application of biochemical principles into clinical terms in an updated way, this book is the unparalleled textbook for medical biochemistry courses in medical, dental and pharmacy programs. Winner of a 2018 Most Promising New Textbook (College) Award (Texty) from the Textbook and Academic Authors Association Offers immediate application of biochemical principles into clinical terms in an updated way Contains coverage of the most current research in medical biochemistry Presents the first solution designed to reflect the needs of both research oriented and clinically oriented medical students